The student's guide to research ethics (Open University Press, 2010)
Ethical Dialogue and Ethical Dilemmas boxes feature throughout the book in order to highlight key issues. There are also further reading sections at the end of each chapter as well as expanded coverage of plagiarism. The Student's Guide to Research Ethics is an invaluable tool for both undergraduate and postgraduate students as well as professionals who research as part of their jobs.